Metal oxide and application thereof

Face-centered cubic structure metal oxide prepared by spray pyrolysis solves the problems of instability and sodium embedding of traditional hydroxide precursors, improves the electrical properties and embedding of the positive electrode materials, and achieves the tightness of the process and structure Combined, reduce costs.

CN119461257APending Publication Date: 2025-02-18HUAYOU NEW ENERGY TECH (QUZHOU) CO LTD +1

Patent Information

Application Number
CN202411154444.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Traditional hydroxide precursors are unstable in the air, are easy to oxidize and have strong hygroscopicity, which affects thermal stability and storage costs, and are difficult to immerse sodium when preparing the positive electrode material, affecting electrical properties.

Method used

It provides a metal oxide with a face-centered cubic structure, which is produced by spray pyrolysis method, and controls its lattice constant and residual stress, so that it has high crystallinity, stability and activity, and promotes the intercalation of sodium ions or lithium ions.

Benefits of technology

Improve the activity of metal oxides, promote the embedding and migration of sodium or lithium ions, improve the comprehensive electrical properties of the cathode material, and realize the close combination of spray pyrolysis technology and crystal structure, reducing time and trial and error costs .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461257A_ABST
    Figure CN119461257A_ABST
Patent Text Reader

Abstract

The invention relates to a metal oxide and application thereof. The metal oxide is of a face-centered cubic structure, the space group is Fd-3m, the lattice constant a of the metal oxide is # imgabs 0 # to # imgabs 1 #, and the tensile residual stress F1 in the metal oxide is 0.105 MPa to 5.51 MPa, or the compressive residual stress F2 in the metal oxide is 1.05 MPa to 8.6 MPa; the metal oxide is prepared by a spray pyrolysis method, and the pyrolysis rate K is 0.361 to 48.611. The metal oxide provided by the invention not only has relatively high crystallinity and stability, but also has high activity, and is beneficial to improving the intercalation of sodium ions or lithium ions when the positive electrode material is prepared, so that the comprehensive electrical property is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a metal oxide and application thereof. Background Art

[0002] Traditional hydroxide precursors are usually hexagonal, unstable in the air, prone to oxidation and hygroscopic, which affects the thermal stability of the precursor and has high storage costs. Partial oxidation will also lead to a reduction in sodium or lithium, which in turn causes a series of problems such as decreased capacity and excessive surface residual alkali. Compared with hexagonal hydroxides, although cubic oxides have high crystallinity and good stability, they have low activity, which makes it difficult to embed sodium when using cubic oxides to sinter positive electrode materials, thus affecting electrical performance. Summary of the invention

[0003] Based on this, it is necessary to provide a metal oxide and its application to address the above problems; the metal oxide not only has high crystallinity and stability, but also has high activity, which is beneficial to improving the embedding of sodium ions or lithium ions when preparing positive electrode materials, thereby improving the overall electrical performance.

[0004] A metal oxide, wherein the metal oxide has a face-centered cubic structure, a space group is Fd-3m, and a lattice constant a of the metal oxide is to The metal oxide has a tensile residual stress F1 of 0.105 MPa to 5.51 MPa, or a compressive residual stress F2 of 1.05 MPa to 8.6 MPa;

[0005] The metal oxide is prepared by spray pyrolysis, and the pyrolysis rate K is 0.361 to 48.611.

[0006] In one embodiment, the pyrolysis temperature T = 938.26-494.18×0.957 ^K .

[0007] In one embodiment, the unit cell density of the metal oxide is ρ=4.806+9×10 -4 ×T.

[0008] In one embodiment, the unit cell density ρ of the metal oxide is 5.22 g / cm 3 Up to 5.55g / cm 3 .

[0009] In one of the embodiments, the diffraction angle of the (220) crystal plane in the metal oxide is θ=30.878-0.001T.

[0010] In one embodiment, the diffraction angle θ of the (220) crystal plane in the metal oxide is 30.10° to 30.42°.

[0011] In one embodiment, the peak intensity ratio of the (311) crystal plane diffraction peak to the (111) crystal plane diffraction peak in the metal oxide is n=5×10 -6 ×T 2 -0.0032×T+2.2835.

[0012] In one embodiment, the peak intensity ratio n of the diffraction peak of the (311) crystal plane to the diffraction peak of the (111) crystal plane in the metal oxide is 1.86 to 3.33.

[0013] In one embodiment, the coordinates of the oxygen atoms in the metal oxide are (x, y, z), where x = y = z = 0.264-1×10 -5 ×T.

[0014] In one embodiment, the coordinates of oxygen atoms in the metal oxide are (x, y, z), wherein x=y=z=0.256 to 0.258.

[0015] In one embodiment, the grain size of the metal oxide is to

[0016] A positive electrode material prepared from the metal oxide precursor as described above.

[0017] A positive electrode sheet comprises a positive electrode current collector and a positive electrode material layer arranged on the surface of the positive electrode current collector, wherein the positive electrode material layer comprises the positive electrode material as described above.

[0018] A secondary battery comprises the positive electrode sheet as described above.

[0019] The metal oxide of the present invention is prepared by a spray pyrolysis method with a certain pyrolysis rate, and satisfies a specific lattice constant and residual stress, so that the metal oxide has a smaller grain size, which is conducive to increasing the number of grain boundaries, introducing more lattice distortions or defects, and providing additional sodium or lithium insertion sites on the basis of maintaining high crystallinity and high stability, thereby improving the activity of the metal oxide, and then promoting the insertion and migration of sodium ions or lithium ions when preparing positive electrode materials, and improving the comprehensive electrical properties. In addition, the metal oxide also realizes a close combination of the spray pyrolysis process and the crystal structure, making it easier to obtain an oxide precursor with a specific crystal structure, and is not easily affected by multiple factors, which is conducive to saving time costs and trial and error costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 This is a scanning electron microscope image of the metal oxide prepared in Example 1 of the present invention;

[0022] Figure 2 is the X-ray diffraction pattern of the metal oxide prepared in Example 1 of the present invention;

[0023] Figure 3 This is a scanning electron microscope image of the metal oxide prepared in Example 2 of the present invention;

[0024] Figure 4 is the X-ray diffraction pattern of the metal oxide prepared in Example 2 of the present invention;

[0025] Figure 5 This is a scanning electron microscope image of the metal oxide prepared in Example 3 of the present invention;

[0026] Figure 6 is the X-ray diffraction pattern of the metal oxide prepared in Example 3 of the present invention;

[0027] Figure 7 This is a scanning electron microscope image of the metal oxide prepared in Comparative Example 1 of the present invention;

[0028] Figure 8 The capacity performance test diagram of the positive electrode material prepared from the metal oxides of Example 1 and Comparative Example 1 of the present invention, wherein A is the capacity performance curve of the positive electrode material prepared from the metal oxide of Example 1, and B is the capacity performance curve of the positive electrode material prepared from the metal oxide of Comparative Example 1;

[0029] Fig. 9 It is a cycle performance test diagram of the positive electrode material prepared from the metal oxides of Example 1 and Comparative Example 1 of the present invention, wherein A is the cycle performance curve of the positive electrode material prepared from the metal oxide of Example 1, and B is the cycle performance curve of the positive electrode material prepared from the metal oxide of Comparative Example 1. DETAILED DESCRIPTION

[0030] For ease of understanding of the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, the purpose of providing these embodiments or examples is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific implementation methods or embodiments and are not intended to limit the present invention.

[0032] The present invention provides a metal oxide, wherein the metal oxide has a face-centered cubic structure, a space group is Fd-3m, and a lattice constant a of the metal oxide is to The metal oxide has a tensile residual stress F1 of 0.105 MPa to 5.51 MPa, or a compressive residual stress F2 of 1.05 MPa to 8.6 MPa;

[0033] The metal oxide is prepared by spray pyrolysis, and the pyrolysis rate K is 0.361 to 48.611, including but not limited to any point value among 0.361, 0.5, 1, 2, 5, 10, 15, 16, 20, 27, 30, 35, 40, 48.611 or any range value between two thereof.

[0034] It can be understood that, based on the face-centered cubic structure of the metal oxide, the space group is Fd-3m, and the lattice constant a=b=c, the present invention does not impose additional limitations on b and c.

[0035] The metal oxide described in the present invention is prepared by a spray pyrolysis method at a certain pyrolysis rate and satisfies specific lattice constants and residual stresses, so that the metal oxide has a smaller grain size, which is beneficial to increase the number of grain boundaries and introduce more lattice distortions or defects. On the basis of maintaining high crystallinity and high stability, it can provide additional sodium or lithium insertion sites, thereby improving the activity of the metal oxide, and further promoting the insertion and migration of sodium ions or lithium ions when preparing positive electrode materials, thereby improving the comprehensive electrical properties.

[0036] In addition, the metal oxide also achieves a close combination of the spray pyrolysis process and the crystal structure, making it easier to obtain an oxide precursor with a specific crystal structure and is not easily affected by multiple factors, which is beneficial to saving time costs and trial and error costs.

[0037] It should be noted that the present invention uses the spray pyrolysis method to The ratio of the pyrolysis time (min) is defined as the pyrolysis rate K, which indicates the relationship between the grain size and the pyrolysis time, and has no unit.

[0038] In one embodiment, the grain size of the metal oxide is preferably to

[0039] In one embodiment, the pyrolysis time is preferably 1 min to 20 min.

[0040] In one embodiment, the pyrolysis temperature T = 938.26-494.18 x 0.957 ^K , more preferably 452°C to 879°C, including but not limited to any point value among 452°C, 500°C, 600°C, 645°C, 700°C, 760°C, 800°C, 879°C or any range value between two thereof, preferably 500°C-850°C.

[0041] It should be noted that the pyrolysis temperature is the system setting temperature of the spray pyrolysis preparation process, that is, the working temperature in the spray pyrolysis device.

[0042] The direction and magnitude of the residual stress F in the metal oxide are closely related to the pyrolysis temperature T in the pyrolysis rate K. When the pyrolysis temperature T is less than 760°C, the residual stress F in the metal oxide is mainly manifested as a tensile residual stress F1, and the tensile residual stress F1 increases with the increase of the pyrolysis temperature T; when the pyrolysis temperature T is greater than or equal to 760°C, the residual stress F in the metal oxide is mainly manifested as a compressive residual stress F2, and the compressive residual stress F2 increases with the increase of the pyrolysis temperature T.

[0043] In one embodiment, the relationship between the residual stress F and the pyrolysis temperature T in the metal oxide preferably satisfies:

[0044] (1) When 452°C≤T<760°C, F1=0.015T-5.895, F1 is the tensile residual stress, and F1 is more preferably 0.885MPa to 5.510MPa;

[0045] (2) When 760°C≤T≤879°C, F2=0.0539T-39.914, F2 is the compressive residual stress, and F2 is more preferably 1.05 MPa to 7.46 MPa.

[0046] It is understood that the formula for residual stress in the present invention is only a quantitative relationship conversion and does not involve unit conversion. In one embodiment, the unit cell density ρ of the metal oxide is proportional to the pyrolysis temperature T in the pyrolysis rate K, satisfying ρ=4.806+9×10 -4 ×T, based on this specific relationship, it is beneficial to further achieve single factor regulation of crystal structure. It can be understood that the present invention uses the unit of g / cm 3 The unit cell density ρ is converted into a unitless value and converted with the unitless thermal decomposition rate K, that is, the formula for unit cell density described in the present invention is only a quantitative relationship conversion and does not involve unit conversion.

[0047] In one embodiment, the unit cell density ρ of the metal oxide is preferably 5.22 g / cm 3 Up to 5.55g / cm 3 , so that the metal oxide has a larger unit cell density, making it easier to obtain a higher positive electrode energy density.

[0048] In one embodiment, the metal oxide has six main characteristic diffraction peaks in the X-ray diffraction pattern, and the corresponding crystal planes are (111), (220), (311), (400), (511), and (440).

[0049] In one embodiment, as the pyrolysis temperature T in the pyrolysis rate K increases, the characteristic diffraction peak corresponding to the (220) crystal plane in the metal oxide shifts to a low angle, and the (220) crystal plane diffraction angle in the metal oxide satisfies θ=30.878-0.001T. Based on this specific relationship, it is beneficial to further achieve single-factor regulation of the crystal structure. It can be understood that the present invention converts the crystal plane diffraction angle θ in units of ° and the pyrolysis temperature T in units of °C into numerical values ​​without units for conversion, that is, the formula for the crystal plane diffraction angle described in the present invention is only a quantitative relationship conversion, and does not involve unit conversion.

[0050] In one embodiment, the diffraction angle θ of the (220) crystal plane in the metal oxide is preferably 30.10° to 30.42°, so that the metal oxide has more lattice distortion or defects, and can provide additional sodium or lithium insertion sites while maintaining high crystallinity and high stability, thereby improving the activity of the metal oxide, and further promoting the insertion and migration of sodium ions or lithium ions when preparing positive electrode materials.

[0051] In one embodiment, the peak intensity ratio of the (311) crystal plane diffraction peak to the (111) crystal plane diffraction peak in the metal oxide is n=5×10 -6 ×T 2 -0.0032×T+2.2835.

[0052] In one embodiment, the peak intensity ratio n of the (311) crystal plane diffraction peak to the (111) crystal plane diffraction peak in the metal oxide is preferably 1.86 to 3.33.

[0053] In one embodiment, the metal atom coordinates in the metal oxide are not affected by the spray pyrolysis process, while the oxygen atom coordinates decrease as the pyrolysis temperature T in the pyrolysis rate K increases. When the oxygen atom coordinates are (x, y, z), x=y=z=0.264-1×10 -5×T, based on this specific relationship, it is beneficial to further achieve single-factor regulation of crystal structure. It can be understood that the present invention converts the pyrolysis temperature T in units of ° C into a unitless value and converts it with the unitless oxygen atomic coordinates, that is, the formula for oxygen atomic coordinates described in the present invention is only a quantitative relationship conversion and does not involve unit conversion.

[0054] In one embodiment, the coordinates of the oxygen atoms in the metal oxide are (x, y, z), preferably x=y=z=0.256 to 0.258, so that the distance between the oxygen atoms and the metal atoms in the metal oxide is closer, which is beneficial to further increase the unit cell density, thereby improving the positive electrode energy density and cycle stability.

[0055] It should be noted that the above X-ray diffraction (XRD) data related to the crystal structure are all original test data of the product without any processing. All products with processed XRD data, if their original data are within the scope of the claims of the present invention, belong to the protection scope of the present invention. The metal atoms in the metal oxide include but are not limited to at least one of Ni, Fe, Mn, Co, Cu, and Zn. It can be understood that the metal oxide precursor of the present invention can be a binary metal oxide, a ternary metal oxide, or a quaternary metal oxide, and the present invention does not limit this.

[0056] The present invention also provides a positive electrode material made from the metal oxide as described above. Preferably, the positive electrode material is a sodium ion battery positive electrode material or a lithium ion battery positive electrode material.

[0057] It should be noted that the preparation method of the positive electrode material refers to the existing method, and the present invention will not elaborate on it.

[0058] The present invention also provides a positive electrode sheet and a secondary battery comprising the positive electrode material, preferably a sodium ion battery, wherein the positive electrode material comprises a positive electrode collector and a positive electrode material layer arranged on the surface of the positive electrode collector, and the positive electrode material layer comprises the positive electrode material as described above.

[0059] In one embodiment, the positive electrode current collector may be a metal foil or a composite current collector, for example, aluminum foil is used as the metal foil; the composite current collector may be formed by forming a metal material on a polymer material substrate.

[0060] It can be understood that the positive electrode material layer also includes a binder and a conductive agent, wherein the binder can be any commercially available binder for positive electrode sheets, or any binder prepared by prior art, and the present invention is not limited to this; the conductive agent can be any commercially available conductive agent for sodium ion batteries.

[0061] The metal oxide and its application will be further described below by the following specific examples. However, it will be understood by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0062] Example 1

[0063] Nickel salt, iron salt and manganese salt are prepared into a mixed metal salt solution in a metal atomic molar ratio of 1:1:1. The mixed metal salt solution is first atomized and then pyrolyzed at a pyrolysis rate of 15.06 to obtain metal oxide. The obtained metal oxide product is represented by a simplified formula of NFM111.

[0064] The surface morphology of the metal oxide prepared in this embodiment is as follows: Figure 1 As shown in the figure, it can be seen that the metal oxide particles have an octahedral structure and the product particle size is relatively uniform. Figure 2 As shown, the relevant test parameters are shown in Table 1, and it can be seen that the metal oxide satisfies: T = 938.26-494.18 × 0.957 ^K , unit cell density ρ = 4.806 + 9 × 10 -4 ×T, (220) crystal plane diffraction angle θ = 30.878-0.001T, (311) crystal plane diffraction peak and (111) crystal plane diffraction peak peak ratio n = 5 × 10 -6 ×T 2 -0.0032×T+2.2835 and the oxygen atomic coordinates x=y=z=0.264-1×10 -5 ×T.

[0065] Example 2

[0066] Nickel salt and manganese salt are prepared into a mixed metal salt solution in a metal atomic molar ratio of 35:65. The mixed metal salt solution is first atomized and then pyrolyzed at a pyrolysis rate of 26.4 to obtain metal oxide. The obtained metal oxide product is represented by a simplified formula of NM3565.

[0067] The surface morphology of the metal oxide prepared in this embodiment is as follows Figure 3 As shown in the figure, it can be seen that the metal oxide particles have an octahedral structure and the product particle size is relatively uniform. Figure 4 As shown, the relevant test parameters are shown in Table 1, and it can be seen that the metal oxide satisfies: T = 938.26-494.18 × 0.957 ^K , unit cell density ρ = 4.806 + 9 × 10-4 ×T, (220) crystal plane diffraction angle θ = 30.878-0.001T, (311) crystal plane diffraction peak and (111) crystal plane diffraction peak peak ratio n = 5 × 10 -6 ×T 2 -0.0032×T+2.2835 and the oxygen atomic coordinates x=y=z=0.264-1×10 -5 ×T.

[0068] Example 3

[0069] Nickel salt, copper salt, iron salt and manganese salt are prepared into a mixed metal salt solution in a metal atomic molar ratio of 2:1:3:3. The mixed metal salt solution is first atomized and then pyrolyzed at a pyrolysis rate of 39.86 to obtain metal oxide. The obtained metal oxide product is represented by a simplified formula of NCFM2133.

[0070] The surface morphology of the metal oxide prepared in this embodiment is as follows Figure 5 As shown in the figure, it can be seen that the metal oxide particles have an octahedral structure and the product particle size is relatively uniform. Figure 6 As shown, the relevant test parameters are shown in Table 1, and it can be seen that the metal oxide satisfies: T = 938.26-494.18 × 0.957 ^K , unit cell density ρ = 4.806 + 9 × 10 -4 ×T, (220) crystal plane diffraction angle θ = 30.878-0.001T, (311) crystal plane diffraction peak and (111) crystal plane diffraction peak peak ratio n = 5 × 10 -6 ×T 2 -0.0032×T+2.2835 and the oxygen atomic coordinates x=y=z=0.264-1×10 -5 ×T.

[0071] Example 4

[0072] Copper salt, iron salt and manganese salt are prepared into a mixed metal salt solution in a metal atomic molar ratio of 2:2:4. The mixed metal salt solution is first atomized and then pyrolyzed at a pyrolysis rate of 1.83 to obtain metal oxides. The obtained metal oxide product is represented by a simplified formula of CFM244.

[0073] The metal oxide prepared in this embodiment was tested. The results are shown in Table 1. It can be seen that the metal oxide satisfies: T = 938.26-494.18 × 0.957 ^K , unit cell density ρ = 4.806 + 9 × 10 -4×T, (220) crystal plane diffraction angle θ = 30.878-0.001T, (311) crystal plane diffraction peak and (111) crystal plane diffraction peak peak ratio n = 5 × 10 -6 ×T 2 -0.0032×T+2.2835 and the oxygen atomic coordinates x=y=z=0.264-1×10 -5 ×T.

[0074] Comparative Example 1

[0075] Nickel salt, iron salt and manganese salt are prepared into a mixed metal salt solution in a metal atomic molar ratio of 1:1:1. The mixed metal salt solution is first atomized and then pyrolyzed at a pyrolysis rate of 49.8 to obtain metal oxide. The obtained metal oxide product is represented by a simplified formula of NFM111.

[0076] The surface morphology of the metal oxide prepared in this comparative example is as follows Figure 7 As shown, it can be seen that the metal oxide particles have an octahedral structure, but the agglomeration phenomenon is serious and the particle size is very uneven. The metal oxide prepared in this comparative example was tested, and the results are shown in Table 1.

[0077] Comparative Example 2

[0078] Nickel salt and manganese salt were prepared into a mixed metal salt solution at a metal atomic molar ratio of 35:65, the mixed metal salt solution was first atomized, and then pyrolyzed at a pyrolysis rate of 0.29 to obtain a metal oxide, and the obtained metal oxide product was expressed as NM3565. The metal oxide obtained in this comparative example was tested, and the results are shown in Table 1.

[0079] Comparative Example 3

[0080] Nickel salt, copper salt, iron salt and manganese salt were prepared into a mixed metal salt solution in a metal atomic molar ratio of 2:1:3:3, the mixed metal salt solution was first atomized, and then pyrolyzed at a pyrolysis rate of 45.2 to obtain a metal oxide, and the obtained metal oxide product was expressed as NCFM2133. The metal oxide obtained in this comparative example was tested, and the results are shown in Table 1.

[0081] Comparative Example 4

[0082] Copper salt, iron salt and manganese salt were prepared into a mixed metal salt solution in a metal atomic molar ratio of 2:4:4, the mixed metal salt solution was first atomized, and then pyrolyzed at a pyrolysis rate of 9.5 to obtain a metal oxide, and the obtained metal oxide product was expressed as CFM244. The metal oxide obtained in this comparative example was tested, and the results are shown in Table 1.

[0083] Table 1

[0084]

[0085] The positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were made into sodium ion button batteries, and the first discharge specific capacity of 0.1C was tested under a voltage of 2 to 4.15V, and the capacity retention rate after 50 cycles was tested under the same voltage condition; 0.1g of the positive electrode material was dissolved in 50mL of pure water, stirred evenly, and then allowed to stand for 1h to measure the pH of the supernatant. The closer the pH value is to neutral, the lower the residual alkali content on the surface is. The test results are as follows: Figure 8 , Fig. 9 And as shown in Table 2.

[0086] Table 2

[0087]

[0088] according to Figure 8 , Fig. 9 As shown in Table 2, the metal oxides prepared in Examples 1 to 4 as positive electrode materials for sodium ion batteries have a high first discharge specific capacity under a voltage condition of 2 to 4.15 V, and still have a capacity retention rate of more than 90% after 50 cycles of the cycle test, and have excellent cycle stability. However, the metal oxides prepared in Comparative Examples 1 to 4 as positive electrode materials for sodium ion batteries have lower specific capacity and stability.

[0089] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0090] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A metal oxide, characterized in that The metal oxide has a face-centered cubic structure, a space group of Fd-3m, and a lattice constant a of the metal oxide is to The metal oxide has a tensile residual stress F1 of 0.105 MPa to 5.51 MPa, or a compressive residual stress F2 of 1.05 MPa to 8.6 MPa; The metal oxide is prepared by spray pyrolysis, and the pyrolysis rate K is 0.361 to 48.

611.

2. The metal oxide according to claim 1, characterized in that Pyrolysis temperature T = 938.26-494.18 × 0.957 ^K .

3. The metal oxide according to claim 2, characterized in that The unit cell density of the metal oxide is ρ=4.806+9×10 -4 ×T.

4. The metal oxide according to claim 3, characterized in that The unit cell density ρ of the metal oxide is 5.22 g / cm 3 Up to 5.55g / cm 3 .

5. The metal oxide according to claim 2, characterized in that The diffraction angle of the (220) crystal plane in the metal oxide is θ=30.878-0.001T.

6. The metal oxide according to claim 5, characterized in that The diffraction angle θ of the (220) crystal plane in the metal oxide is 30.10° to 30.42°.

7. The metal oxide according to claim 2, characterized in that The peak intensity ratio of the (311) crystal plane diffraction peak to the (111) crystal plane diffraction peak in the metal oxide is n=5×10 -6 ×T 2 -0.0032×T+2.2835.

8. The metal oxide according to claim 7, characterized in that The peak intensity ratio n of the (311) crystal plane diffraction peak to the (111) crystal plane diffraction peak in the metal oxide is 1.86 to 3.

33.

9. The metal oxide according to claim 2, characterized in that The coordinates of oxygen atoms in the metal oxide are (x, y, z), where x = y = z = 0.264-1×10 -5 ×T.

10. The metal oxide according to claim 9, characterized in that The coordinates of oxygen atoms in the metal oxide are (x, y, z), wherein x=y=z=0.256 to 0.

258.

11. The metal oxide according to claim 1 or 2, characterized in that The crystal size of the metal oxide is to 12. A positive electrode material prepared from the metal oxide precursor according to any one of claims 1 to 11.

13. A positive electrode sheet, characterized in that: It comprises a positive electrode current collector and a positive electrode material layer arranged on the surface of the positive electrode current collector, wherein the positive electrode material layer comprises the positive electrode material as claimed in claim 12.

14. A secondary battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 13.

Citation Information

Patent Citations

  • Metal oxide precursor and preparation method and application thereof

    CN118223127A

  • Metal oxide precursor and preparation method and application thereof

    CN118422336A

  • Method of preparing electrode composition having a carbon-containing-coated metal oxide, electrode composition and electrochemical cell

    US20030207178A1

  • Metal-oxide thin-film transistor and method for fabricating same, display panel, and display device

    US20240194747A1

Cited By

  • Metal oxide and use thereof

    EP4772470A1

  • Metal oxide and use thereof

    WO2026040744A1